Effect of Melatonin and in Combination with CIDR on Reproductive Performance in anestrus lactating Iraqi buffaloes (Bubalus bubalis). - M., Al-Hamedawi, T.; A., Hatif, S. (The Iraqi Journal of Veterinary Medicine, 2020)
The present study was performed on 30 lactating Iraqi buffaloes suffered from ovarian inactivity diagnosed by rectal palpation during 60-90 days postpartum, aged between 3-6 years at Al-Thahab Al-Abiad village / Abu-Graib / Baghdad province during the period from February- June 2020 . The animals divided into three equal groups (10 buffaloes for each one). 1st group treated with melatonin implants (90mg/animals/SC) for 30 days but 2nd group treated with melatonin implants conjugated with CIDR (1.38 gm) in day 20 for 10 days, 3rd group without treatment (control group). The results in this study were recorded animal response 90%, 100% and 50% in 1st ,2nd and 3rd groups respectively with superior significantly (P<0.01) for treated groups compared with control group and 8.26±1.33, 7.15±0.97 and 160.5±14.31 days which represented the duration of response in 1st ,2nd and 3rd groups respectively with significantly differences (P<0.01) related with control, but the number of services per conception recorded insignificantly in all groups, while the pregnancy rate revealed significant differences (P<0.01) in treated group compared with control group. Finally the days open recorded 153.6±6.72, 142.8±7.45 and 217.3±19.56 in 1st, 2nd and 3rd groups respectively with highly significantly (P<0.01) in treated group compared with control group. In conclusion in present study, the role of melatonin in improvement of reproductive performance in anestrus lactating Iraqi buffaloes suffered from ovarian inactivity was safe and effective